HUBUNGAN STIMULASI LINGKUNGAN KELUARGA DENGAN KEMAMPUAN MENGENAL LAMBANG BILANGAN ANAK USIA DINI - Sopiawati; Syahrul Ismet (STKIP Subang, 2026)
This study aims to determine the relationship between family environment stimulation (the role of parents) and the ability to recognize number symbols in children aged 4–5 years at Al-Fikri Kindergarten, North Bengkulu. This type of research is non-experimental with a quantitative approach using the correlational method. The research subjects consisted of 14 students (8 boys and 6 girls) along with their parents at Al-Fikri Kindergarten, Tebat Pacur Village, North Bengkulu Regency. Data collection techniques utilized a closed-ended questionnaire with a Likert scale to measure the role of parents (variable X) and a performance observation sheet to measure children's ability to recognize number symbols (variable Y). The data were statistically analyzed using a correlation test. This was evidenced by a correlation coefficient value (rₛ) of 0.685 (p = 0.008 < 0.05), with a coefficient of determination value (rₛ) of 0.469. This proves a positive and significant relationship in the strong category, where family environment stimulation contributes to explaining 46.9% of the variation in the ability to recognize number symbols among Group B children at Al-Fikri Kindergarten, North Bengkulu.